The development of mobile learning application-based comprehensive guidance and counseling media in basic service (EDasbk) for elementary school teachers - Muhammad Akmal Malik; Abdul Saman; Muhammad Anas (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2023)
This research is aimed to know; (1) the need for comprehensive guidance and counseling media based on a mobile learning application (EDasbk) for teachers in basic services; (2) an appropriate prototype of comprehensive guidance and counseling media based on a mobile learning application (EDasbk); (3) the validity and practicality of comprehensive guidance and counseling media based on a mobile learning application (EDasbk) for elementary school teachers. This is a research and development study with interview and questionnaire as data collection technique. The data was analyzed quantitatively and qualitatively. This study found that (1) most classroom teachers could not conduct guidance and counseling optimally and did not completely know their task to guide, so this mobile application-based comprehensive guidance and counseling media (EDasbk) was needed by elementary school teachers (2) there was an appropriate prototype of comprehensive guidance and counseling media developed through an andromo-mobile app builder for Android, and mobile learning application (EDasbk) of the 1.0.4 stable version. (3) the validity and practicality of the mobile learning application (EDasbek) through the first product testing was implemented in a small group and involved two experts showing a very high result. It means that the mobile learning application (EDasbk) is accepted and can be used by classroom teachers to give guidance and counseling to the elementary school students.